Effectiveness Of Traffic Operations On Increasing Helmet Use In Gorontalo City - Ayis Nusi (Estudiante Law Journal, 2021)
This study aims to determine the effectiveness of the implementation of traffic operations to increase compliance with helmet use for motorcyclists in the city of Gorontalo. The type of research used in this research is empirical legal research. This research is located at the Gorontalo City Police Traffic Unit. The data used in this study were obtained using observation and interview techniques. The results of this study indicate that there are still many violations of the use of helmets so that the implementation of traffic operations to increase compliance with using helmets for motorbike riders in the city of Gorontalo has not been effective, other efforts need to be made by the Satlantas Polres Gorontalo City, namely: Police friends of children, school security patrols , Provide socialization and traffic education, Install billboards containing the rules and the importance of helmets, Cooperate with agencies.